The Influence of Corporate Social Responsibility (CSR) on Company Performance and Company Reputation as a Mediation Variable (Study on Companies in the Sri-Kehati Index Year 2017- 2021) - Yumna Syaza Kani Putri; Wirmie Eka Putra; Susfa Yetti (DINASTI RESEARCH, 2023)
This research was carried out to determine the relationship between the influence of Corporate Social Responsibility (CSR) on company performance and company reputation as a mediating variable in the Sri-Kehati Index Company in 2017-2021 using smartpls as a tool for processing data. The results of data processing found that Corporate Reputation had a significant positive effect on Company Performance, Corporate Social Responsibility (CSR) had a significant negative effect on Company Reputation, then Corporate Social Responsibility (CSR) had an insignificant negative effect on Company Performance, and finally Corporate Reputation had a significant negative effect. As mediation in the relationship between Corporate Social Responsibility (CSR) and Performance Company.